Association of designer drug use and sudden cardiac death: a systematic review - Shrouk Mohamed Ali; Ghadeer M. M. Abdelaal; Dena Mohamed Naguib Abdel Moawed; Shaimaa A. Shehata (Egyptian Journal of Forensic Sciences)
Abstract Background Sudden death (SD) is defined as a non-violent, unexpected death occurring within 24 h of symptom onset, with no clear alternative explanation. It affects all age groups and can stem from both toxicological and non-toxicological causes. Among the toxicological contributors, the use of new designer drugs has emerged as a leading cause of death. This systematic review aims to estimate the prevalence of SD associated with new designer drugs, explore the pharmacological mechanisms underlying their effects, and identify the pathophysiological processes that lead to sudden death. The ultimate goal is to support the development of evidence-based risk mitigation strategies. Main body A total of 28 studies published between 2012 and 2024 were included. The majority of cases involved young adult males. The most commonly reported substances were synthetic cannabinoids (nine published articles) and synthetic opioids (eight published articles), followed by other categories such as synthetic cathinones and synthetic new psychoactive substances. Outcomes measured across studies included toxicological findings and postmortem reports. Conclusions The current evidence suggests that certain populations—especially young males—are at heightened risk for SD associated with designer drug use. Further research is essential to improve risk stratification and guide the development of preventive and clinical response strategies.